2011
DOI: 10.1108/09684881111125069
|View full text |Cite
|
Sign up to set email alerts
|

Principals' and teachers' perceptions of quality management in Hong Kong primary schools

Abstract: PurposeThe purpose of this paper is to examine the perceptions of a sample of Hong Kong principals and teachers of the extent to which quality management (QM) has been effectively implemented in primary schools. The features of QM improvement implemented in Hong Kong primary schools include: values and duties, systems and teams(ST) resources and changes(RC) and meeting pupil needs and empowering staff.Design/methodology/approachA quantitative, survey questionnaire was adopted in this study. A total of 322 resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
0
8
0
2
Order By: Relevance
“…Kaiseroglou and Sfakianaki (2020) emphasize, among other things, the importance of commitment by both leadership and employees regarding TQM implementation and the necessity for both human and financial resources to facilitate smooth and successful TQM implementation. Cheng and Yau (2011) and Bouranta et al (2021) further indicate the importance of resources as a source of quality in education.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Kaiseroglou and Sfakianaki (2020) emphasize, among other things, the importance of commitment by both leadership and employees regarding TQM implementation and the necessity for both human and financial resources to facilitate smooth and successful TQM implementation. Cheng and Yau (2011) and Bouranta et al (2021) further indicate the importance of resources as a source of quality in education.…”
Section: Discussionmentioning
confidence: 97%
“…The results match the general notion provided by the scholarly literature. For example, Cheng and Yau (2011) find that sources of quality in education include, among others and in an appropriate combination, well-maintained buildings, use of the latest technology and a well-balanced curriculum. Elahi and Ilyas (2019) also associate quality with, among other things, activities related to the development of curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, it can be argued that raising the awareness of the instructors about quality assurance systems, standards, and accreditation may enable the instructors to attach more importance to the quality standards and to the activities which are put into practice to increase the quality of education at IEPs. Cheng and Yau (2011) found that principals had more positive perceptions of quality management than teachers did. They suggested that having more administrative experience and higher levels of professional education could be the reasons for adopting a more positive attitude towards change at schools.…”
Section: Discussionmentioning
confidence: 99%
“…Peningkatan dilakukan melalui pelatihan dan pengembangan karakter. Hal ini juga ditemukan oleh Cheng & Yau (2011) yang memfokuskan pengembangan sekolah pada pemberdayaan staf karena guru/staf yang berkualitas akan mampu membawa kemajuan sekolah.…”
Section: Hasil Dan Pembahasanunclassified